2004
DOI: 10.1016/s1607-551x(09)70245-1
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Arthroscopy for Symptomatic Total Knee Arthroplasty

Abstract: Thirty-one knees with symptomatic total knee arthroplasty were diagnosed and treated arthroscopically. There were 18 knees with soft tissue impingement and 13 knees without. There were 16 knees with painful arthroplasty and range of motion (ROM) greater than 90 degrees. Hypertrophied synovitis with or without impingement was more easily found by arthroscopy in this group than in the other 15 knees with the chief complaint of limited ROM, where more remarkable fibrotic tissue with intra-articular adhesion was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Another study concluded that arthroscopy is helpful for intra-articular diagnosis, and for better range of motion, and proved to be a safe, reliable and effective method of treatment [42]. The rehabilitation was also found to be easier and much quicker [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study concluded that arthroscopy is helpful for intra-articular diagnosis, and for better range of motion, and proved to be a safe, reliable and effective method of treatment [42]. The rehabilitation was also found to be easier and much quicker [22].…”
Section: Discussionmentioning
confidence: 98%
“…Klinger et al [27] performed a study on a series of 27 patients, and his results showed that arthroscopy after total knee replacement gives reliable expectation for improvement in function, decrease in pain and improvement for knee scores for most patients. Another study concluded that arthroscopy is helpful for intra‐articular diagnosis, and for better range of motion, and proved to be a safe, reliable and effective method of treatment [42]. The rehabilitation was also found to be easier and much quicker [22].…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue impingements of several pathological entities have been reported. Patellar clunk syndrome (PCS) [ 10 - 13 ] and patellar synovial hyperplasia (PSH) [ 10 , 14 , 15 ] are the two main entities of impingement; however, other types of impingement including soft tissue impingement at the intercondylar notch [ 16 ], impingement of the posterior cruciate ligament stump [ 14 , 17 , 18 ], and arthrofibrosis [ 17 - 20 ] have also been reported. In these diseases, if the patients are resistant to conservative treatment, arthroscopic surgery is indicated instead of revision surgery in many cases [ 10 , 12 , 18 ].…”
Section: Introductonmentioning
confidence: 99%